Pengalaman Komunikasi Kelompok KLa Project dan Eksistensinya Selama 32 Tahun - Nur Desilawati (Program Studi Pendidikan Musik FBS UNP, 2021)
The 1990s are considered a major force on fashion, music and screens. At that time, in Indonesia various bands were born, developed and reached a golden age. One of them is the KLa Project, which is still surviving until the age of 32. This study aims to determine the experience of group communication in the KLa Project band in an effort to maintain their existence for 32 years in the Indonesian Music scene. The method used is qualitative with a phenomenological approach. The research subjects consisted of the main research subjects, namely KLa Project personnel, namely Ignatius Bagaskoro Katon, Romulo Radjadin, Adi Adrian and Ahmad Ari Suharto. Supporting research subjects were also taken in this study, namely the crew and management of the KLa Project, as well as several other fellow musicians who are related to the KLa Project. The results show that communication between personnel in the KLa Project music group or band is the most important and fundamental thing. The group communication is also dynamic and there is a change in communication patterns during the early formation and journey of the KLa Project, namely from 1986-1987 to 2000, with the communication situation between personnel in 2001.